Fabricated germanium-doped silica optical fibres: a novel dose indicator for clinical blood irradiation - Mohd Noor, Noramaliza; Idris, Faridah; Ku Bakar, Ku Shaidaton Akmar (Penerbit Universiti Kebangsaan Malaysia, National University of Malaysia Press, 2025)
TA-GVH disease represents a potential adverse effect associated with blood transfusions, highlighting the importance of irradiating blood components within defined limits to effectively mitigate this risk. The recommended irradiation doses range from 25 to 50 Gy, with a peripheral threshold established at 15 Gy. This study explores the feasibility of using fabricated germanium-doped (Ge-doped) silica-based optical fibres as dose indicators during clinical blood transfusions. Two types of 2.3 mol% Ge-doped optical fibres were tested: cylindrical (CF) and flat (FF). Calibration was performed using a Cobalt-60 gamma-ray machine across a dose range of 5 to 50 Gy. Clinical trials were conducted using a Cesium-137 source blood irradiator. A central dose of 25 Gy was delivered to real adult blood bags, which were exposed to gamma rays for 9 min and 56 s. Thermoluminescence (TL) signals from the fibres were measured with a HarshawTM 3500 TLD reader, and compared with EBT-XD film and conventional dose indicator stickers. The study found no statistically significant difference among dosimeters, with a p-value of 0.285 (p > 0.05, 95% Confidence Level) for the 25 Gy dose. Mean errors were 3.4% for CF and 4.3% for FF when compared to EBT-XD film. These results indicate that Ge-doped optical fibres offer precise, quantitative measurements of blood irradiation doses, unlike conventional dose stickers which provide only qualitative visual indicators. This innovative dosimetry approach shows significant potential as a cost-effective, reusable, and highly sensitive alternative for clinical blood irradiation.